The Correlation between Serum Total Adiponectin and Hemoglobin in Type 2 Diabetic Patients without Microalbuminuria - S. Khamis, Ammar; H. Ali, Shatha; I. Al-Lehibi, Khalid (Iraqi Journal of Pharmaceutical Sciences, 2017)
Low serum total adiponectin is associated with a high incidence of type 2 diabetes or coronary artery disease in the general population. Paradoxically, serum total adiponectin is elevated in patients with chronic kidney disease (CKD), such as overt diabetic nephropathy. The current study aimed to investigate whether or not anemia to be dependently associated with serum level of total adiponectin in non-albuminuric male patients with type 2 diabetes . The study included 42 type 2 diabetic male patients. Anemia was deï¬ned as hemoglobin (Hb) below 14.0g/dL. All the patients were without microalbuminuria, to exclude diabetic nephropathy. The diabetic patients were divided into 2 groups according to the hemoglobin level in addition to 16 healthy control group. Serum total adiponectin levels were measured by a sandwich enzyme-linked immunosorbent assay. In all 42 patients with type 2 diabetes, serum total adiponectin levels were correlated positively with serum creatinine and age, whereas, negative correlations were found with Hb. A stepwise regression analysis demonstrated that among several signiï¬cant variables, Hb had the strongest independent inï¬‚uence on total adiponectin (Î² = -0.512, at P < 0.01). In conclusion, anemia could be associated with a marked elevation in serum total adiponectin levels of diabetic patients without a detectable nephropathy (-ve microalbuminuria).Key words: Type2 Diabetes, Adiponectin, Hemoglobin,Microalbuminuria.